A Study of Popular Artificial Intelligence Python Modules in Open Source Projects - Reno, Camila; Cardoso, João Marcos; Cordeiro, Viviane; Meirelles, Paulo; Francisco, Phyllipe (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM), 2025)
The increase in the use and popularity of Artificial Intelligence (AI) is directly related to the rise of the Python language, which is recognized for its simplicity and efficiency in AI projects. In this context, this study aimed to analyze the use of AI modules in public GitHub repositories. For this, the repository mining technique was applied using the Anonymous tool. A total of 142 popular repositories were analyzed, and we identified 17 that contained a set of predefined AI modules of interest. The most popular AI module identified was TensorFlow, present in just over 94% of these repositories. This highlights TensorFlow’s dominance in AI projects, due to its robustness, active community, and integration with other tools. Furthermore, the predominance of this library reflects developers’ preference for well-supported solutions with extensive practical applications. Our results complement the lists of popular libraries available online in grey literature, supporting professionals in making informed decisions when choosing libraries. They can align their projects with the most common and successful open-source practices.